Islamic Finance-Growth Nexus: Evidence from Indonesia - Firsty Izzata Bella; Imron Mawardi; Ishma Amelia (Universitas Islam Negeri Raden Mas Said Surakarta, 2022)
Previous work on the financial industry, which covers the entire financial services sector and is related to economic growth, has remained limited. This present study empirically analyzed the growth of Indonesia’s three main sectors of the Islamic Financial Industry (Islamic Capital Market, Islamic Banking, and Islamic non-bank Financial Industry) towards economic growth between 2014Q1 and 2021Q3. The quarterly data was processed through the ARDL Bound-test for cointegration and Error Correction Model (ECM). The research revealed three of the four research variables (sharia stock, Sukuk, and sharia insurance) that significantly affect GDP, while Islamic banking shows no significant effect on GDP. As a result, Indonesian Islamic banks must optimize funds for the productive sector. Future policies should consider maximizing the role of the Islamic financial industry to accelerate economic growth.